Effect of hyperbilirubinemia on Some Physiological parameters in infantile in Karbala city - Abid, Qasim Hamadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Given that these substances' levels are essential for informing medicalpersonnel about the body's reaction to the different treatments beingadministered, this study was planned to assessment some physiologicalvariations to infants infected with hyperbilirubinemia. This will help themedical staff manage the condition properly with lower morbidity andmortality. In this study, 60 patients and 40 healthy controls (clinicallyevaluated by a specialist physician) are selected from males who are only1 year old. This study conducted in Al-hussein medical city Hospital inKarbala city. This study showed that significant decrease in weight,hemoglobin and packed cell volume in patients in comparison withhealthy, while noted significant increase in total white blood cells inpatients comparison with healthy, while showed there are insignificantchange in red blood cells and platelet.